The resurgence of Corynebacterium diphtheriae: A rare case of infective endocarditis (Indian Journal of Case Reports, 2020)
Corynebacterium species or “diphtheroids” are often considered as non-pathogenic components of the normal skin flora when isolated from blood culture. Invasive diseases like infective endocarditis with Corynebacterium diphtheriae are an unusual presentation. We report the case of a 34-year-old man with a medical history of prosthetic valve replacement 12 years back who presented with acute visual loss both eyes and high-grade fever. Echocardiography revealed small particles in the left ventricular outflow tract and the left ventricle probably small detached vegetations. Blood cultures were positive for non-toxigenic C. diphtheriae. The patient was diagnosed as prosthetic valve endocarditis caused by non-toxigenic C. diphtheriae considering the whole clinical picture, including the patient’s medical history, physical examination, and blood cultures.